Determinan Underpricing Saham IPO di BEI: Peran ROA, DER, dan Reputasi Underwriter - Zilbram Devano, Nico (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study examines the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), and underwriter reputation on the level of IPO underpricing among companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. A quantitative approach with multiple linear regression analysis was employed using 137 companies as the sample, selected through purposive sampling. Underpricing is measured as the percentage difference between the offering price and the first trading day closing price. The empirical results reveal that ROA has a significant negative effect on underpricing (p-value = 0.001), indicating that firms with higher profitability provide a positive signal to investors, thereby reducing information uncertainty in the market. Conversely, DER (p-value = 0.479) and underwriter reputation (p-value = 0.054) show no significant influence, suggesting that leverage and the credibility of underwriters are not the primary considerations for investors in making IPO investment decisions. These findings highlight profitability as a more dominant determinant in reducing underpricing than capital structure or underwriter reputation.